Investigation of Urban Parks and their Connection with the Real Estate Sector in Cuiabá, Mato Grosso - Oliveira, Poema Bidarra; Paula, Diana Carolina Jesus de; Godoy, Jeane Aparecida Rombi de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The continuous demographic growth in urban areas is one of the aspects that highlights, above all, the debate on environmental issues related to the development of cities and real estate expansion close to green areas. It is worth highlighting that green areas tend to increase the value of nearby properties, increasing their sales value or attracting new investments, which use green spaces as a business strategy. Therefore, urban parks become an element of appreciation for the region in which they are located. In this sense, the objective of this study is to investigate urban parks located in the northern region of Cuiabá/MT, from 2005 to 2020. To do this, it was necessary to classify the soil according to use and occupation and use the Generic Values Plan , to check the value per m² defined by the Municipality of Cuiabá. As a result, it was possible to classify urban use and occupation, as well as the value per square meter of streets in the period studied. It is observed that among the parks studied in the northern region, Massairo Okamura Park was the most valued during the years analyzed.